(mbqr’/ mbqr) in the Nabataean Sinaitic Inscriptions and the Dead Sea Scrolls - Al-Salameen, Zeyad Mahdi; Al-Qananweh, Ekhlass Khalid (Jordan Journal for History and Archaeology, 2024)
This article examines and analyses the word mbqr’ that appears in some Nabataean Sinaitic inscriptions. The word is discussed in its both etymological and idiomatic contexts, based on specialized Semitic dictionaries and published Semitic inscriptions. Special attention is paid to the lexical data of the Dead Sea Scrolls